Circ-Vps41 positively modulates Syp and its overexpression improves memory ability in aging mice - Li, Yibo; Wang, Hongfang; Gao, Yanjing; Zhang, Runjiao; Liu, Qing; Xie, Wenmeng; Liu, Ziyu; Geng, Dandan; Wang, Lei (Frontiers in Molecular Neuroscience, 2022)
Age is an established risk factor for neurodegenerative disorders. Aging-related cognitive decline is a common cause of memory impairment in aging individuals, in which hippocampal synaptic plasticity and hippocampus-dependent memory formation are damaged. Circular RNAs (circRNAs) have been reported in many cognitive disorders, but their role in aging-related memory impairment is unclear. In this study, we aimed to investigate the effects of circ-Vps41 on aging-related hippocampus-dependent memory impairment and explore the potential mechanisms. Here, D-galactose was used to produce a conventional aging model resulting in memory dysfunction. Circ-Vps41 was significantly downregulated in D-galactose-induced aging in vitro and in vivo. The overexpression of circ-Vps41 could upregulate synaptophysin (Syp), thereby promoting the synaptic plasticity and alleviating cognitive impairment in aging mice. Mechanistically, we found that circ-Vps41 upregulated Syp expression by physically binding to miR-24-3p. Moreover, the miR-24-3p mimics reversed the circ-Vps41 overexpression-induced increase in Syp expression. In conclusion, overexpression of circ-Vps41 alleviated the synaptic plasticity and memory dysfunction via the miR-24-3p/Syp axis. These findings revealed circ-Vps41 regulatory network and provided new insights into its potential mechanisms for improving aging-related learning and memory impairment.